Community Empowerment: Interpreting Election for Baduy Indigenous People - Al Arif Fitriana, Mohamad Noor Fajar (Probono and Community Service Journal, 2024)
This research explores the unique perspective of the Baduy indigenous community onIndonesian elections. While voting is a constitutional right for all citizens, the Baduy peopleview the electoral process through the lens of their deeply rooted cultural philosophy. Theyadhere to the principle of lunang ("following the winner"), signifying their willingness toaccept and support the elected leader with an open heart. This study argues that theirpractice of ngasuh ratu/raja and ngayak menak (guiding and obeying the leader) reveals aprofound form of civic engagement that prioritizes community harmony and nationalstability over partisan politics. This challenges conventional understandings of democraticparticipation and offers a valuable perspective on the importance of cultural context inpolitical processes.